The relationship between the smoking habits and the frequency of quiting and dependent personality traits among health professionals in a training hospital - Temel, Adil; Dilbaz, Nesrin; Bayam, Göksel; Okay, Tuncer; Şengül, Cem (Journal of Dependence, 2004)
Cigarette smoking habit or nicotine dependency is an important problem because of adverse effects on health. It needs emergent and effective precautions. Three million people die around the world every year because of smoking related diseases. The prevalence of cigarette smoking among the general population and health professionals in Turkey is higher than the developed countries. Therefore health professionals need more education on the subject of smoking, smoking related diseases and methods of cessation. We planned this research to evaluate the smoking behaviors, the rate of quitting and the relationship between dependent personality traits and cigarette smoking. We performed the research with a total of 270 health personnel who accepted to join research. We evaluated their smoking habits, cessation, degree of addiction and rate of quitting by using a questionnaire form composed of Cage, Four C, Fagerstrom tests. As a measure of ‘dependent personality’, a separate part of the MMPI personality inventory included the MMPI-Dy test for dependency consisting of 57 questions. Among the health staff included in this study, there were 50% active smokers; 8.9% had quit smoking, and 41.1% did not smoke. Cigarette smoking ratio was 57.4% among males and 43.3% among females. Dependent personality characteristics viewed from the point of smoking shows about the same mean values for smokers and non-smokers. However those who quitted smoking got significantly low dependant personality (MMPI-Dy) scores. We conclude that dependent personality characteristics does not make a difference within smokers and non-smokers but those who gets lower dependent personality points succeed to quit smoking more than others. We may assume that according to this result, cigarette cessation programs focusing also on to the dependent personality characteristics could be more successful.
Keywords: Cigarette smoking; tobacco; nicotine dependence; Fagerstrom test; dependent personality; health staff